Memoir as Medicine and Ceremony: Historical Trauma, Mental Illness, and Survivance in Terese Marie Mailhot’s Heart Berries - Sarah Dees (Journal of Religion & Society Supplement Series, 2026)
Terese Marie Mailhot’s 2018 bestselling memoir Heart Berries has been hailed by reviewers. In addition to its literary merit, Heart Berries is valuable for scholars and students of Native North American religion and health. While religion is not the main subject of the memoir, the topic is woven throughout. In addition, illness features prominently in the text. This article is motivated by two primary questions: First, how are autobiography and memoir useful for understanding elements of Native American religion and spirituality? Second, what can autobiographical texts by Indigenous authors illuminate about the relationship between religion, spirituality, history, mental health, and wellbeing? Offering insights into contemporary Indigenous lived religion, Heart Berries illuminates connections between individual and communal (un)wellness. Further, it highlights the influence of settler colonialism on Indigenous health outcomes. For Indigenous communities, addressing historical trauma is necessary for healing—and religion has played a role in each.